Local Democracy and Community Participation: The Role of Information and Communication Technology - Ii Sumantri (Global Writing Academica Researching & Publishing, 2021)
This study aims to analyze the role of information and communication technology (ICT) in increasing community participation in local democracy. The research method used is a qualitative method with a literature study approach by collecting data from various sources related to the implementation of ICT in community participation in local democracy. The results of the analysis show that ICT has an important role in increasing community participation in local democracy. ICT enables community participation in various activities such as elections, participation in discussion forums, and access to public information. ICT also makes it easy for the government to convey public information and receive input from the public. However, the challenges in implementing ICT to increase community participation in local democracy also need attention. These challenges include people's access to technology which is still limited and the lack of participation from certain community groups such as the elderly, the elderly, and the disabled. This study recommends the importance of developing ICT infrastructure and training for the community regarding the use of ICT in participation in local democracy. In addition, there needs to be a special effort to involve community groups that are less involved in local democratic participation in the use of ICT.